Analisis Peran Camat dalam Penyelenggaraan Pemerintahan di Kecamatan Pallangga Kabupaten Gowa - Ade, Andi Muhammad; Yunus, Rabina; Rusli, Andi Muhammad (Program Studi Ilmu Pemerintahan Fisip Unhas, 2013)
Abstract: This study aims to determine the role of the tasks and functions district particularly to coordinate community development activities in the District Pallangga Gowa and explain the factors that affect the tasks and functions camat in coordinating community development activities in the District Pallangga Gowa. Data collection methods used in this study were interviews, literature study and observation. Data were analyzed qualitatively. The results were analyzed in the duties and functions camat in coordinating community development activities as follows: encourage community participation to participate in development planning within the scope of the sub-district development planning forum in villages / wards, To provide guidance and oversight of all work units both government and private agencies that have work programs and community development activities in the work area districts, Evaluating the community development activities in the districts of whether committed by government or private work units. Factors that affect the tasks and functions camat in coordinating community development activities, namely: camat leadership skills, work environment, personal skills, human resources, and facilities.Keywords: subdistrict head, community empowerment, gowaAbstrak: Penelitian ini bertujuan untuk mengetahui peran pelaksanaan tugas dan fungsi camat khususnya dalam mengkoordinasikan kegiatan pemberdayaan masyarakat di Kecamatan Pallangga Kabupaten Gowa dan menjelaskan faktor- faktor yang mempengaruhi pelaksanaan tugas dan fungsi camat dalam mengkoordinasikan kegiatan pemberdayaan masyarakat di Kecamatan Pallangga Kabupaten Gowa. Data yang diperoleh dianalisis secara kualitatif. Hasil penelitian dianalisis dalam tugas dan fungsi camat dalam mengkoordinasikan kegiatan pemberdayaan masyarakat dengan rincian: mendorong partisipasi masyarakat untuk ikut serta dalam perencanaan pembangunan lingkup kecamatan dalam forum musyawarah perencanaan pembangunan di desa/kelurahan, Melakukan pembinaan dan pengawasan terhadap seluruh unit kerja baik pemerintah maupun swasta yang mempunyai program kerja dan kegiatan pemberdayaan masyarakat di wilayah kerja kecamatan, Melakukan evaluasi terhadap kegiatan pemberdayaan masyarakat di wilayah kecamatan baik yang dilakukan oleh unit kerja pemerintah maupun swasta. Faktor-faktor yang mempengaruhi pelaksanaan tugas dan fungsi camat dalam mengkoordinasikan kegiatan pemberdayaan masyarakat, yaitu: kemampuan kepemimpinan camat, lingkungan kerja, kemampuan pribadi, sumberdaya manusia, serta sarana dan prasarana.Kata kunci: camat, pemberdayaan masyarakat, Gowa